2015
DOI: 10.1002/anie.201411483
|View full text |Cite
|
Sign up to set email alerts
|

A TEMPO‐Free Copper‐Catalyzed Aerobic Oxidation of Alcohols

Boran Xu,
Jean‐Philip Lumb,
Bruce A. Arndtsen

Abstract: The copper-catalyzed aerobic oxidation of primary and secondary alcohols without an external N-oxide co-oxidant is described. The catalyst system is composed of a Cu/diamine complex inspired by the enzyme tyrosinase, along with dimethylaminopyridine (DMAP) or N-methylimidazole (NMI). The Cu catalyst system works without 2,2,6,6-tetramethyl-l-piperidinoxyl (TEMPO) at ambient pressure and temperature, and displays activity for un-activated secondary alcohols, which remain a challenging substrate for catalytic ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 49 publications
(57 reference statements)
2
76
0
3
Order By: Relevance
“…37 The consumption of oxygen gas was probed via gas-uptake measurements within a sealed reaction vessel, while simultaneously monitoring aldehyde formation via in situ ATR-IR spectroscopy. The data in Figure 3 show that the quantity of O 2 consumed tracks directly with the amount of aldehyde produced throughout the reaction, with an O 2 :aldehyde stoichiometry of approximately 1:2.…”
Section: Resultsmentioning
confidence: 99%
“…37 The consumption of oxygen gas was probed via gas-uptake measurements within a sealed reaction vessel, while simultaneously monitoring aldehyde formation via in situ ATR-IR spectroscopy. The data in Figure 3 show that the quantity of O 2 consumed tracks directly with the amount of aldehyde produced throughout the reaction, with an O 2 :aldehyde stoichiometry of approximately 1:2.…”
Section: Resultsmentioning
confidence: 99%
“…251253 This reactivity has been effectively exploited in effecting catalytic oxidations of alcohols and phenols. 254–256 …”
Section: Dicopper Compoundsmentioning
confidence: 99%
“…In 2013, Herres-Pawlis et al presented catalytic copper(I) model systems supported by bis(pyrazolyl)methane ligands which exhibit room temperature stable peroxo intermediates [20]. More recently, Lumb et al demonstrated catalytic conversions of different monophenols to a variety of organic products [21][22][23][24][25][26]. During the last years our group published a number of new copper(I) complexes functioning as model systems for tyrosinase [2,19,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%